PELAKSANAAN URUSAN KEBUDAYAAN SEBAGAI BENTUK OTONOMI DAERAH KHUSUS ISTIMEWA YOGYAKARTA DALAM NEGARA KESATUAN REPUBLIK INDONESIA - Azahra, Widya Oka (Hukum dan Masyarakat Madani, 2022)
AbstractEach region has the authority and responsibility to carry out its respective regional affairs. The implementation of regional autonomy makes it easier for local governments to carry out their duties. In addition there is also special regional autonomy, one of which is the Special Region of Yogyakarta, which is a region that has a privileged legal position based on history and rights of origin according to the 1945 Constitution of the Republic of Indonesia, to regulate and administer special powers. This legal research uses the normative-empirical legal research method. So that in data collection, secondary data and primary data are needed. The results of this study are related to the implementation of the Yogyakarta Special Region Regulation Number 3 of 2017 concerning Cultural Maintenance and Development, this study aims to become a benchmark for the government and related parties to evaluate themselves in terms of implementation if there are still deficiencies and also to provide information related to the implementation of Yogyakarta Special Region Regulation Number 3 of 2017 concerning Cultural Maintenance and Development whether it has been going well or not. In addition, it is also to introduce one of the noble traditions that exist in the Special Region of Yogyakarta, namely Sekaten. The Sekaten celebration which is held aims to spread Islam as well as to provide meaning in practicing the traditions that live in society.Keywords: Sekaten Custom; Culture; Special Region of Yogyakarta; Special Regional Autonomy.AbstrakSetiap daerah memiliki kewenangan dan tanggung jawab menyelenggarakan urusan daerahnya masing-masing. Diberlakukannya otonomi daerah menjadikan kemudahan bagi pemerintah setempat dalam melaksanakan tugas-tugasnya. Selain itu terdapat pula otonomi daerah khusus salah satunya ialah Daerah Istimewa Yogyakarta merupakan daerah yang memiliki keistimewaan kedudukan hukum berdasarkan oleh sejarah dan hak asal-usul menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, untuk mengatur serta mengurus kewenangan istimewa. Penelitian hukum ini menggunakan metode penelitian hukum normatif-empiris. Sehingga dalam pengumpulan data maka dibutuhkan data sekunder dan data primer. Hasil penelitian ini ialah terkait dengan pelaksanaan Peraturan Daerah Istimewa Yogyakarta Nomor 3 Tahun 2017 tentang Pemeliharaan dan Pengembangan Kebudayaan, penelitian ini bertujuan untuk menjadi salah satu tolak ukur bagi pemerintah maupun para pihak terkait untuk mengevaluasi diri dalam hal pelaksanaannya jika memang masih terdapat kekurangan dan juga untuk memberikan informasi terkait dengan pelaksanaan Peraturan Daerah Istimewa Yogyakarta Nomor 3 Tahun 2017 tentang Pemeliharaan dan Pengembangan Kebudayaan apakah telah berjalan dengan baik atau tidak. Selain itu juga untuk memperkenalkan salah satu tradisi luhur yang ada di Daerah Istimewa Yogyakarta yaitu Sekaten. Perayaan Sekaten yang diselenggarakan bertujuan untuk menyebarluaskan agama islam juga memberikan makna dalam mengamalkan tradisi-tradisi yang hidup dalam masyarakat.  Kata Kunci: Adat Sekaten; Budaya; Daerah Istimewa Yogyakarta; Otonomi Daerah Khusus.
Keywords: Sekaten Custom; Culture; Special Region of Yogyakarta; Special Regional Autonomy.